Relative output factors of different collimation systems in truebeam STx medical linear accelerator - Do, Duc Chi; Tran, Ngoc Toan; Hill, Robin; Nguyen, Do Kien (Nuclear Science and Technology, 2021)
The IAEA TRS483 and TRS398 Code of Practices (CoP) were used to calculate relative output factors for small photon beams of 6X, 6XFFF energies shaped by High Definition Multileaf Collimator (HDMLC), jaws and cones mounted on TrueBeam STx medical linear accelerator (Varian Medical Systems), respectively. A comparison between these results were made. The results show a large discrepancy in relative output factor curves found among different collimation systems of the same equivalent field sizes and between the CoPs. Therefore, the specific beam modelling in treatment planning system for each type of the collimation system to be used for small fields maybe required for better computational accuracy.